2019
DOI: 10.3892/ol.2019.10548
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑589 serves as a tumor suppressor microRNA through directly targeting metastasis‑associated protein 2 in breast cancer

Abstract: Triple-negative breast cancer (TNBC) has a poorer outcome compared with that of other subtypes of breast cancer, and the discovery of dysregulated microRNA (miRNA) and their role in tumor progression has provided a new avenue for elucidating the mechanism involved in TNBC. Previous studies have revealed that aberrant expression of miRNA-589 (miR-589) was frequently observed in various types of cancer. However, the expression and function of miR-589 in TNBC has not been well illustrated. In the present study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…More importantly, the function of miRNA in BC has been revealed by various studies. For example, miRNA-589 functions as a tumor inhibitor via directly targeting metastasis-associated protein 2 (MTA2) in BC 27 . MiR-29b-3p promotes the proliferation and migration of MDA-MB-231 cells (TNBC cells) via down-regulating TRAF3 28 .…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the function of miRNA in BC has been revealed by various studies. For example, miRNA-589 functions as a tumor inhibitor via directly targeting metastasis-associated protein 2 (MTA2) in BC 27 . MiR-29b-3p promotes the proliferation and migration of MDA-MB-231 cells (TNBC cells) via down-regulating TRAF3 28 .…”
Section: Discussionmentioning
confidence: 99%
“…10,11 For example, miR-589 served as a tumor suppressor in TNBC by targeting the metastasis-associated protein 2. 12 Recent study showed that the overexpression of miR-29b-3p promoted the progression of TNBC via downregulating TNF Receptor Associated Factor 3 (TRAF3) and activating nuclear factor-kappa B signaling. 13 Interestingly, an increasing body of evidence demonstrated the tumor suppressive potential of miR-331-3p in multiple cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Given the regulatory role of the miR-589-5p/HDAC5 pathway in proliferation, migration, invasion, and tumorigenicity in NSCLC cells, this pathway was suggested as a new prognostic biomarker and therapeutic target against NSCLC (Liu et al, 2017). It was also found that the expression of miR-589-5p down-regulated in other cancers such as prostate (Ji et al, 2019) and triple-negative breast cancer (TNBC) (Chu, 2019). These results suggest that miR-589-5p through oncogenic or tumor-suppressive functions may be a potential biomarker in OSCC and different cancers.…”
Section: Discussionmentioning
confidence: 89%